АГРОЕКОЛОГІЧНІ АСПЕКТИ ВИКОРИСТАННЯ МІКРОБНОГО ПРЕПАРАТУ БІОГРАНУ ДЛЯ КУКУРУДЗИ - Борулько , Р.О. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2008)
The results of research of polifunctional granular preparation Biogran efficiency for maize at the different agrofons are represented. Positive influence of biopreparation on productivity of culture and quality of harvest, reduction of the biogenic elements losses with filtration waters due to more effective absorption of macroelements by the inoculating plants are take place.